A Study of Depression and Quality of Life in Patients of Lichen Planus. (23rd February 2015) - Sawant, Neena S.; Vanjari, Nakul A.; Khopkar, Uday; Adulkar, Satish
Abstract : The precise cause of lichen planus is unknown, but the disease seems to be immunologically mediated. It is a psychocutaneous disorder. Due to scarcity of Indian studies in this field, we decided to study in patients of lichen planus the prevalence of depression and quality of life with comparison of the same in both the genders. Patients diagnosed as having lichen planus by consultant dermatologist were enrolled after informed consent and ethics approval. 45 patients were screened, of which 35 who satisfied the criteria were taken up for the study. A semistructured proforma was designed to collect the necessary information with administration of dermatology life quality index and Beck's depression inventory. While 25% were depressed with females being more affected than males, quality of life was impaired in more than 90% patients. Impairment was maximum due to symptoms and illness feelings, disturbed daily activities, or work and time consumption in treatment. There was a strong association between depression and impairment in quality of life in both the genders. This study helps in early identification of psychological problems in lichen planus patients and in planning their future course of management, hence reducing the lack of productivity and improving the prognosis and quality of life.